Distinguishing Painted dog (Lycaon pictus) footprints from Domestic dog (Canis lupus familiaris) and Hyaena (Crocuta crocuta) footprints in the field – in search of a quantitative method - Scharis, Inger (Institutionen för fysik, kemi och biologi, 2011)
Population estimation is an important task in all wildlife conservation. Such estimations are often difficult in low-density species such as big carnivores. The painted dog (Lycaon pictus) is an endangered species and the first aim of IUCNs action plan is to assess the size and the distribution of the remaining population. This study is the first step towards a quantitative method to distinguish painted dog footprints from footprints of feral domestic dogs and hyaenas. Footprint photographs were collected and digitally processed and total pad area and angles between the digits and backpad of the paw were measured. Both the pad area and the angles show a statistically significant difference between the species. However, further analysis shows that there is no significant difference in pad area between painted dog females and domestic dog males. Size of the pads alone is therefore not suitable as a measure to determine the species from an unknown footprint. The angles between backpad and digits seem to be more suitable to distinguish between species. Therefore, a combination of pad size and the angle between backpad and digits might be useful to estimate the species from an unknown footprint in the field.